2017
DOI: 10.3168/jds.2016-12381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscular injections of folic acid, vitamin B12, or both, on lactational performance and energy status of multiparous dairy cows

Abstract: The purpose of this experiment was to gain understanding on changes in energy partitioning when folic acid and vitamin B supplements, alone or combined, were given by weekly intramuscular injections from 3 wk before the expected calving date until 7 wk postpartum. Twenty-four multiparous cows were assigned to 6 blocks of 4 cows each according to previous 305-d lactation yield to either 0 or 320 mg of folic acid and 0 or 10 mg of vitamin B in a 2 × 2 factorial arrangement. Plasma concentration of folates was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 45 publications
11
46
3
1
Order By: Relevance
“…Serum folate concentration is an accurate indicator of the status of body folate [18]. In the present study, serum concentration of folate increased linearly with dietary FA supplementation throughout the experiment, which is consistent with previous studies in dairy cows [10,19,20] and sheep [21]. The folate concentration was higher in twin born ewes than triplet born ewes at 90 days after mating, this may be due to the higher folate requirement as gestation progressed with larger litter size from mating to early gestation.…”
Section: Discussionsupporting
confidence: 91%
“…Serum folate concentration is an accurate indicator of the status of body folate [18]. In the present study, serum concentration of folate increased linearly with dietary FA supplementation throughout the experiment, which is consistent with previous studies in dairy cows [10,19,20] and sheep [21]. The folate concentration was higher in twin born ewes than triplet born ewes at 90 days after mating, this may be due to the higher folate requirement as gestation progressed with larger litter size from mating to early gestation.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, limited response was observed for ADG, ruminal total VFA concentration, apparent total-tract NDF and ADF digestibility and blood folate concentration with addition of BT in the RPFAþ diet and for blood methionine concentration with addition of RPFA or/and BT. Similarly, Duplessis et al (35) reported that intramuscular injection of FA did not affect plasma methionine concentration in dairy cows.…”
Section: Discussionmentioning
confidence: 92%
“…The higher blood folate and lower Hcy indicated that dietary FA was absorbed efficiently, and more Hcy was transformed into cysteine and methionine to participant in protein synthesis . Similarly, Duplessis et al, (2016) found that plasma folate increased and Hcy decreased with FA supplementation in dairy cows. The response of blood folate and Hcy to HCP diet suggested that the absorption of FA was promoted with increasing dietary CP level, but further study was required to support this suggestion.…”
Section: Blood Metabolites and Hormone Contentmentioning
confidence: 88%
“…Similarly, other studies found no influence of increasing dietary CP level on blood glucose in calves (Liu et al, ; Lohakare et al, ). However, Duplessis, Lapierre, Pellerin, Laforest, and Girard () reported that plasma glucose and insulin were unaltered in prepartum dairy cows, but increased in post‐partum dairy cows with FA supplementation. The data suggested that the response of blood glucose and insulin to FA supplementation was associated with the physiological status of animals.…”
Section: Discussionmentioning
confidence: 99%